The agricultural value chains and poverty reduction: Assessment of Nigeria - Onuoha, Onyinyechi Josephine; Sakanko, Musa Abdullahi; Baba, Sunday; Moses, Adesanya Babatunde (Lapai Journal of Economics, 2023)
Development has phases and occurs not just through putting and pushing necessary policies and programmes. The agricultural value chains as a Century programme aims to rebrand farmers’ access to the markets and resources they need to produce and sell their crops at a higher price. This helps to increase their income, which can then be used to improve their living conditions and reduce poverty. On this note, the study investigated the impact of the agricultural value chains on poverty reduction in Nigeria from 1990 to 2022. The study employed the Autoregressive Distributive Lag model (ARDL). The empirical findings revealed that the agricultural value chains have inversely impacted poverty reduction in Nigeria in the short and long run. As a stop-gap measure, the government should promote agricultural value chain development to achieve organisational and institutional innovations that will empower people. Providing more inputs, technical training, and financial service to the farmers to increase the production outlet should be encouraged.